Pengembalian Fungsi Daerah Sekitar Sungai: Konflik dan Tantangan Dalam Proses Regenerasi Sungai Cikapundung, Bandung - Mahardini, Sevina (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
The study examines the conflicts and challenges in a public space refunctioning project frequently found among the government and the civil society, taking a case study in Cikapundung river. The theme of the study is â€œjeux dâ€™acteursâ€ in French or stakeholder strategy in English. The study employs qualitative method by interviewing stakeholders and experts, supported by secondary data from the Government, stakeholder notes, workshops, and personal blogs. Stakeholder analysis has identified the interests of each actor involved in the CikapundungÂ river bank project. Economic interest came from the government and investors, social interest came from non-governmental organizations and local communities, while environmental issues have been the concern of non-governmental organizations and creative organizations. Emerging conflicts between the civil society and the government has been a sign of failure to establish good project governance (gouvernance du projet in French). Stakeholders could not present their concerns in more positive ways, as sources of ideas to improve the river. It was concluded that as a result of lack in integration of interests, a proper model of public space in the Indonesian context is difficult to find.